Eficiência dos óleos de andiroba, copaíba e pinhão manso na melhoria da resistência da madeira de Pinus elliottii a organismos xilófagos - Sousa, Sara Freitas de (2016)
Many are the compounds used to increase the natural resistance of wood against xylophagous organisms. Natural products have been studied to ensure the sustainability of the environment, human health, and reduce the use of traditional products. The objective of this research was to evaluate the efficiency of andiroba, copaiba and pinhão-manso oils in the biological resistance of the wood of Pinus elliottii. The andiroba and copaíba oils were got from communities of Santarém city – Pará, Brazil and the pinhão-manso was got from Tamanduá farm, situated in Santa Terezinha – Paraíba, Brazil. Determined the physical characteristics (pH, acid rate, viscosity and density), toxicity test in culture medium and accelerated decay in laboratory (brown and white rot fungi), soft-rot fungi and termite resistance. To evaluate the efficiency used oils pure and fortified with iodine sublimed. Evaluated the volatilization and leaching effects these ones to the xylophagous degrading organisms. In General, with the increase of iodine in andiroba and copaiba oils, viscosity and density increase, in addition to lower the pH. The increase of iodine provided better oils efficiency, being it verified by lower weight loss, except in the termite resistance assay of dry wood, in which the pure oils provided greater resistance to wood. In all trials, the untreated wood was more damaged. It was noted that the volatilization and leaching influenced negatively the efficiency of oils in some treatments, in the tests carried out.